Explaining Sandwich Generation Phenomena in the Modernity Dimension - Aang Supriatna; Mohammad Rindu Fajar Islamy; Kokom Siti Komariah; Muhamad Parhan; Adila Hafidzani Nur Fitria (Jurnal Studi Sosial dan Politik, 2022)
This study aims to explore the community's view of the phenomenon of Sandwich Generation in the dimension of modernity. The increasing number of population in Indonesia also gives rise to a new phenomenon, namely the Sandwich Generation. The Sandwich Generation phenomenon has been introduced since the 90s, especially among women who work to maintain two generations simultaneously. Responding to this ongoing phenomenon by finding out how the public responds to sandwich generation by distributing questionnaires in the form of Google Forms to various groups of people to analyze the results of the community's responses to the current phenomenon. The results of the analysis show that there are still many misconceptions regarding this phenomenon, which is considered one of the forms of child exploitation. This happens because of a lack of knowledge about how a child is obliged to his parents, being the sandwich generation is not a disgrace but a good opportunity to be devoted to both parents and must live it sincerely so that what is obtained can be a blessing.